ADJECTIVE CLASSES IN NORTHEAST ASIA: REVISITING THE JAPANESE AND KOREAN LANGUAGES - Tanaka de Lira, Marcus Vinicius (Universidade Federal do Amazonas - Ufam, 2020)
Descriptions of languages from Northeast Asia must frequently grapple with the question of whether they should recognise the existence of an adjective class in its lexical system. This discussion has been present in studies of languages from the region, such as Ainu (REFSING, 1986; SHIBATANI, 1990), Korean (CHANG, 1996; BYON, 2009; YEON e BROWN, 2011) and Nivkh (NEDJALKOV e OTAINA, 2013; GRUZDEVA, 1998; MATTISSEN, 2003) and, in Brazil, it has been present in the field of Japanese studies thanks to descriptions such as Suzuki (2016). In order to better understand the difficulties involved in the description of adjective classes in the region, the lexical classes whose classification has been disputed in Korean and Japanese have been analysed. After the application of 17 morphosyntactic and semantic criteria found in Dixon (2010) e Givón (2001), it has been noted that it is possible to spot more differences than similarities in the grammatical behaviour of verbs and adjectives in both languages, justifying the division into two different lexical classes. Descrições de línguas do nordeste asiático frequentemente precisam lidar com a questão do reconhecimento ou não de uma classe adjetival em seu sistema lexical. Essa discussão tem estado presente nos estudos de línguas da região como Ainu (REFSING, 1986; SHIBATANI, 1990), falado no norte do Japão; Coreano (CHANG, 1996; SOHN, 2004; SOHN, 1999; YEON e BROWN, 2011), falado na península coreana; e Nivkhe (NEDJALKOV e OTAINA, 2013; GRUZDEVA, 1998; MATTISSEN, 2003), falado ao norte do Japão. No Brasil, essa mesma discussão tem estado presente na área de estudos japoneses devido a descrições como a de Suzuki (2016). A fim de melhor entender as dificuldades envolvidas na descrição das classes adjetivais da região, foram analisadas em coreano e japonês as classes lexicais cuja classificação são objeto de debate. Aplicaram-se 17 critérios morfossintáticos e semânticos encontrados em Dixon (2010) e Givón (2001) e, após a análise, constatou-se que é possível verificar mais diferenças do que semelhanças no comportamento gramatical de verbos e adjetivos em ambas as línguas, justificando a divisão em duas classes lexicais.